2020
DOI: 10.1136/bmjopen-2020-040069
|View full text |Cite
|
Sign up to set email alerts
|

Association between homicide rates and suicide rates: a countrywide longitudinal analysis of 5507 Brazilian municipalities

Abstract: ObjectiveTo estimate the association between homicide and suicide rates in Brazilian municipalities over a period of 7 years.DesignWe conducted a longitudinal ecological study using annual mortality data from 5507 Brazilian municipalities between 2008 and 2014. Multivariable negative binomial regression models were used to examine the relationship between homicide and suicide rates. Robustness of results was explored using sensitivity analyses to examine the influence of data quality, population size, age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Homicide and suicidal behavior are significantly correlated in Europe [ 7 , 17 , 26 ], but not in the Americas and Asia [ 7 , 17 ] based on global research studies. Within the regional studies, the direction of the associations between suicidal behavior and homicide depended on geographical locations with positive associations mostly observed in Europe and no or a negative association in the Americas [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homicide and suicidal behavior are significantly correlated in Europe [ 7 , 17 , 26 ], but not in the Americas and Asia [ 7 , 17 ] based on global research studies. Within the regional studies, the direction of the associations between suicidal behavior and homicide depended on geographical locations with positive associations mostly observed in Europe and no or a negative association in the Americas [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven country-level variables were identified for inclusion in the multilevel analysis. These included the Gini coefficient (GC), Gross Domestic Product (GDP) per capita, the pupil-to-teacher ratio in primary schools, the population density, the intentional homicide rate, laws regarding suicide and the night light index [ 11 , 21 , 26 , 30 , 32 , 45 , 48 ]. These variables were selected based on their importance as key socio-economic indicators as well as their potential to influence mental wel-being at population levels [ 4 , 11 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Any violence, whether witnessed or directly experienced, has been strongly associated with developing depression and suicidal behaviour, in both high-income countries and LMICs [9]. At the municipality-level in Brazil, higher homicide rates have even been associated with higher suicide rates [10]. There is less research assessing whether those with depression and prior experience of violence have a different likelihood of having their depression diagnosed and treated.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies showed that suicide rates were positively related to the business cycle, while homicide rates were negatively related. However, other studies suggested a positive and parallel rate relationship between suicide and homicide ( Holinger & Klemen, 1982 ; Machado et al, 2020 ; McKenna et al, 1997 ). Although these inconsistencies are, in part, explained by different sampling approaches, sample sizes and analytic strategies, there are also suggestions that the rate relationship between suicide and homicide varies across countries, and time periods (e.g., Bills & Li, 2005 ; Fountoulakis & Gonda, 2017 ).…”
Section: Introductionmentioning
confidence: 94%